Evaluasi Pengguna HIS dengan Metode TAM di Wilayah Kerja Rumah Sakit Dr. Cipto Mangunkusumo - Revina Purnaningrum; Bangga Agung Satrya; Muhammad Fuad Iqbal; Noor Yulia (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Hospital information systems are technologies used in hospital information management. Dr. Cipto Mangunkusumo Hospital has kept up with technological developments by using HIS which is used to simplify the service process in the medical record unit from incoming patients to outpatients. The purpose of this study is to find out the overview based on the Technology Acceptance Model (TAM) dementia, which is an information system theory of how users can accept and utilize technology. The RME evaluation considers five perceptions, namely perceived ease of use, perceived usefulness, attitude toward using, behavioral intention, and actual technology use. The method of this study is quantitative description research and the object of this study is 96 Hospital Information System (HIS) respondents. The results of this study show that as many as (61.5%) respondents who received HIS and (38.5%) who have not received HIS with details of the perceived ease of use HIS obtained (75%), perceived usefulnesss (70.8%), Attitude toward using was obtained (79.2%), behavioral intention was obtained (62.5%) and in terms of Actual Technology Use as many as 70.8% used every day with a duration of 3 hours per day. It can be concluded that the perception of HIS users has gone well and provided benefits for officers including increased productivity in doing work, but there are still several shortcomings so that there is a need for monitoring and socialization of users who are still not skilled in using HIS and developing HIS features that are more responsive to the needs of health workers and improving technological infrastructure so that HIS can run more easily.